Waste seashell as calcium oxide catalyst for bio-oil production from empty fruit bunch
Oil palm waste could be converted into bio-oil through pyrolytic process due to its renewable resource to ensure continuity and capacity for renewable-energy solution. It is a great challenge to convert empty fruit bunch (EFB) into liquid product which is bio-oil in an effective way. In addition, catalyst was added in the pyrolysis process to evaluate the effect of catalytic pyrolysis EFB towards the yields of bio-oil, biochar and gas as pyrolysis product yields. Therefore, this study was conducted to evaluate the effect of waste seashell based calcium oxide (CaO) as catalyst using a fixed bed reactor for bio-oil production from EFB. The optimization process parameters such as particle size (A) pyrolysis temperature (B) and nitrogen flow rate (C) were investigated through central composite design (CCD) with bio-oil considered as the response. The pyrolysis temperature (B) was considered as the most significant parameter followed by particle size (A). From the optimization study, an optimum pyrolysis temperature of 628 °C, nitrogen flow rate of 250 ml/min and the particle size of 710-1000 μm produced 44.1% of biooil. The functional group analysis showed the presence of acid, ketone, polycyclic aromatic hydrocarbons (PAHs), alcohol and carbonyl groups. The pH of bio-oil obtained from the catalytic process was higher than the non-catalytic process was higher than the non-catalytic process which varies from pH 3.5 to pH 4.3. Therefore the acidity of bio-oil was reduced in presence of Cao catalyst from seashell. The effect of viscosity of bio-oil obtained by catalytic process was also enhanced from 20.5 to 37.8 cP. Therefore, CaO catalyst from waste seashell affected the production of bio-oil in terms of quantity and quality. Morphological analysis of catalyst from waste seashell showed well organized, porous grains with uniform surface. The compositions of catalyst were 3.0 % C, 40.1 % O2 and 56.9 % Ca, and total composition of the catalyst was 98.5 %. The surface area of the calcined seashell catalyst, pore size and pore volume were 10.22 m2g-1, 122.92 Å and 0.0341 cm3g-1 respectively. Therefore, calcined waste seashell as calcium oxide catalyst is rich in calcium suitable as a catalyst which is very cost effective and green technology for the production of bio-oil from waste to wealth.